Hegel: método e política - Rosa, Bruno Ferreira (Revista Eletrônica Estudos Hegelianos, 2018)
The aim of this article is to pursue the relations between method and politics in Hegel’s political thought trying to show how the concepts of ‘ actuality’  (Wirklichkeit ) and ‘ possibility’  (Möglichkeit ) articulate not only the systematic perspective of Hegel’s  political work with the perspective of the process, but also provides the mediation capable of connecting the dialectical reconstruction of that structure that embodies freedom with the critic of these structures. Hegel avoids thus to conceptualize politics as the formulation of demands towards reality with any kind of anchorage in its dialectics. By this way, we think it will be clear why Hegel adopts a reformist perspective in politics.